Heading the ball - Luhtanen, P. (coachesinfo.com)
About the heading the ball in soccer, which is a skill which is unique to the game of soccer, as few other ball games exist in which the ball can be played with the head. Heading is an important skill in the game, for advancing the ball downfield, intercepting a pass, or as a shot on goal. Since the ball in soccer is airborne for a large percentage of playing time, heading is the main method of playing the airborne ball. In elite soccer competition, a large percentage of the goals are scored from headers.